How to make your iWeb sites to a dedicated host. IN Create. - Bohon, Cory.
Move your iWeb sites to a dedicated hosting solution before Apple pulls the plug on MobileMe.
Keywords: iWeb (Web site development tool); Apple MobileMe; Dropbox